ASPEK-ASPEK FILOSOFIS ZAKAT PROFESI - Firdaweri, Firdaweri (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2014)
Professional zakat is kind of zakat that be paid fromprofessionals‟ fees after certain nisab. In term ofprofessional zakat, a profession is classified into twocatagories which are: first, personal private profession;and second, the profession that depend on otherpeople or institution. It formulation is referredlogically to a common conduct of agricultural zakat;which is type of zakat that farmers paid after theirharvest without any waiting times‟ requirement. Fromthis common practice, some peoples do an analogicaleffort to convert it to be a new form of zakat. A newterminology of zakat which is „professional zakat‟ thatreally close to agricultural zakat in term of it laws‟,purposes and requirement. Beginning here thecontroversies came up. These mentioned issues will bediscussed further on the writing.